Guide to the Naturalized and Invasive Plants of Southeast Asia - Witt, Arne (CABI, 2017)
Despite the significant impacts of alien plant species (IAS), there has not been a concerted effort to tackle the problem across the region. This can mainly be ascribed to a lack of policy, little awareness and limited capacity at a national and regional level. The UN Environment-Global Environment Facility project, 'Removing Barriers to Invasive Species Management in Production and Protection Forests in SE Asia', which was active in Cambodia, Indonesia, the Philippines and Vietnam, identified these barriers and produced this Guide which will go a long way to creating awareness about invasive plants, their impacts and how best to manage them. This Guide will serve as an invaluable aid in the identification, mapping, monitoring, and management of IAS that are already present in ASEAN member states, or which may become problematic in the future, due to increased trade and travel, economic development and climate change. It is hoped that this Guide would trigger similar efforts in other countries in Southeast Asia as the region moves toward socio-economic integration.